Roles of steroid hormones in oviductal function. Issue 3 (March 2020) - Barton, Brooke E; Herrera, Gerardo G; Anamthathmakula, Prashanth; Rock, Jenna K; Willie, Anna M; Harris, Emily A; Takemaru, Ken-Ichi; Winuthayanon, Wipawee
Abstract : The oviduct (known as the fallopian tube in humans) is the site for fertilization and pre-implantation embryo development. Female steroid hormones, estrogen and progesterone, are known to modulate the morphology and function of cells in the oviduct. In this review, we focus on the actions of estrogen and progesterone on secretory, ciliated, and muscle cell functions and morphologies during fertilization, pre-implantation embryo development, and embryo transport in humans, laboratory rodents and farm animals. We review some aspects of oviductal anatomy and histology and discuss current assisted reproductive technologies (ARTs) that bypass the oviduct and their effects on embryo quality. Lastly, we review the causes of alterations in secretory, ciliated, and muscle cell functions that could result in embryo transport defects.